A Soft- Computing Approach for Multi Criteria Project Selection Problem with Grey Number - BAKSHI, TULI; SARKAR, BIJAN; SANYAL, SUBIR KUMAR (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Multi-criteria decision support systems are used in various fields of human activities. In every alternative multi-criteria decision making problem can be represented by a set of properties or constraints. The properties can be qualitative & quantitative. For measurement of these properties, there are different unit, as well as there are different optimization techniques. Depending upon the desired goal, the normalization aims for obtaining reference scales of values of these properties. This paper deals with the multi-attribute Complex Proportional Assessment of alternative. In order to make the appropriate decision and to make a proper comparison among the available alternatives Analytic Hierarchy Process (AHP) under fuzziness and COPRAS method with grey numbers has been used. The uses of AHP is for analysis the structure of the project selection problem is used under fuzziness and to assign the weights of the properties and the COPRAS-G method is used to obtain the final ranking and select the best one among the projects. To illustrate the above mention methods survey data on the expansion of optical fiber for a telecommunication sector is reused. The decision maker can also used different weight combination in the decision making process according to the demand of the system.COPRAS-G method is used to evaluate the overall efficiency of a project with the criterion values expressed in terms of intervals. It is based on the real conditions of decision making and applications of the grey number theory.